'Creating assessments as an active learning strategy: what are students' perceptions? A mixed methods study' – a supplementary letter. Issue 1 (1st January 2019) - Cahilog, Zhen; Lei, Harry Yeuk Hei; Al-Musawi, Safa
ABSTRACT: This is a supplementary letter in response to Kurtz and colleagues' recent publication exploring the creation of assessments for active learning, with the aim of discussing some of the important points raised by the authors and improvements based on our experience as final year medical students.